Kings of pastry [videorecording (DVD)] - Hegedus, Chris; Pennebaker, D. A.; Pfeiffer, Jacquy; Canonne, Sebastien; Rigollot, Philippe; Lazard, Regis (First Run Features, 2010)
Follows chef Jacquy Pfeiffer, co-founder of Chicago's French Pastry School, as he journeys back to his childhood home in Alsace, France to practice for the Meilleurs Ouvriers de France pastry competition.